One-step combustion synthesis of C/MgO composite powders with MgO nanofibers. Issue 10 (15th May 2021) - Li, Kaidi; Xiao, Guoqing; Ding, Donghai; Chong, Xiaochuan; Luo, Jiyuan; Chen, Xing; Bai, Bing; Ren, Yun
Abstract: C/MgO composite powders were prepared by combustion synthesis using magnesium oxalate and magnesium powders as raw materials. The phase composition and microstructure of the composite powders were investigated by X-ray diffraction (XRD), field-emission scanning electron microscopy/energy dispersive spectroscopy (FESEM/EDS), high-resolution transmission electron microscopy (HRTEM) and Raman spectroscopy. The synthetic mechanism was explored through TG-FTIR and combustion front quenching techniques. It was found that the C/MgO composite powders contained a large quantity of MgO nanofibers. When the molar ratio of magnesium oxalate and magnesium was 1:4, the carbon content of the product reached a maximum of 9.45 wt %. In the composite powders, cubic MgO particles were encapsulated by a thin carbon layer, and there was a tiny gap between MgO and the carbon layer; a large number of MgO nanofibers with aspect ratios of 80–100 were found. The cubic MgO particles of the products are the direct decomposition of MgC2 O4, and the MgO nanofibers are the reaction product of gaseous Mg and CO2 /CO at high temperature. Meanwhile, the carbon deposited on the MgO particles can inhibit the grain growth of MgO particles and result in the refinement of MgO particles. The uniform dispersion of carbon and the weak C/MgO interface combine, making the composite powders a potential additive for low-carbon MgO–C refractories with excellent thermal shock resistance.